Analysis of Project Performance Criteria for Design and Build Contract - Taurista Yuristanti; I Putu Artama Wiguna; Herry Budianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The design and build (DB) project delivery system recently begins to be widely used for road projects in Indonesia. It has some advantages such as shorter completion time, lower cost growth, lower schedule growth, and better performance in terms of quality. The complexity of DB projects and the lack of complete rules and regulations in this field have caused the implementation of DB projects to face various challenges and problems. Thus, DB projects need to be evaluated to improve their performance. The purpose of this study is to provide the concept of DB project performance, performance criteria, and performance indicators that used to carry out a performance assessment. The analysis was done based on a literature review and interviews. There are fifteen indicators generated from this analysis. The indicators divided into three parts: design phase performance, construction phase performance, and overall project performance and three criteria: results quality, resource usage, and objectives achieved.